Kajian Psikologi Sastra dalam Naskah Perempuan dan Ilusinya Karya Adhyra Pratama sebagai Pertimbangan Bahan Ajar Materi Drama Jenjang SMA Kelas 11 - Adinda Dewi Lestari; Aliza Maula; Dias Sena Hidayat; Adita Wirada Putra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Literature is the author's means of expressing ideas and ideas. Literary works are usually created from the author's experiences or other people's stories (Musliah, Halimah, & Mustika, 2019). It can be concluded that literary works and humans have an inseparable relationship because literature is a reflection of human life which includes thoughts, feelings, attitudes, behavior, knowledge, responses and human imagination (Safitri, 2014). The ego, as a controller, functions to balance identity needs with the realities of the external world, often through coping and adjustment mechanisms. This drama is included in the type of tragedy drama because it shows the character in a sad or gloomy state, which usually occurs because the character is in a serious situation and is not beneficial to the character.